Posthuman bodies - Halberstam, Jack, 1961-; Livingston, Ira, 1956- (Indiana University Press, 1995)
"It is a collection of essays that takes up, in a mostly affirmative way, various challenges to the coherence of the "human body" as a figure through which culture is processed and oriented." Partial contents : The end of the world of White Men ; Class and its close relations : identities among women, servants, and machines ; Soft fictions and intimate documents : can feminism be posthuman? ; Reproducing the posthuman body : ectogenetic fetus, surrogate mother, pregnant man ; The seductive power of science in the making of deviant subjectivity ; Phantom and reel projections lesbians and the (serial) killing-machine ; "Death of the family."
Keywords: Bürger, Christa -- 1935- -- Postmoderne; Human body -- Social aspects.; Human body -- Symbolic aspects.; Human body (Philosophy); Body image.; Sex symbolism.; Sex in popular culture.; Humanism -- History -- 20th century.; Postmodernism.; Humanism.; Popular culture.; Body Image; Humanism; Popular Culture; Corps humain -- Aspect social.; Corps humain -- Aspect symbolique.; Corps humain (Philosophie); Image du corps.; Symbolisme sexuel.; Sexualité dans la culture populaire.; Humanisme -- Histoire -- 20e siècle.; Postmodernisme.; Humanisme.; Culture populaire.; humanism.; popular culture.; 42.85 physical anthropology.; 17.90 literature in relation with other areas of science and culture.; HEALTH & FITNESS -- Beauty & Grooming.; Body image; Human body -- Social aspects; Human body -- Symbolic aspects; Postmodernism; Sex in popular culture; Sex symbolism; Kultur; Körper; Kulturwandel; Technischer Fortschritt; Postmoderne; Menselijk lichaam.; Seksualiteit.; Populaire cultuur.; 1900-1999; Electronic books.; History